2018
DOI: 10.1182/blood-2017-08-801738
|View full text |Cite
|
Sign up to set email alerts
|

Lactadherin promotes microvesicle clearance to prevent coagulopathy and improves survival of severe TBI mice

Abstract: Coagulopathy is common in patients with traumatic brain injury (TBI) and predicts poor clinical outcomes. We have shown that brain-derived extracellular microvesicles, including extracellular mitochondria, play a key role in the development of TBI-induced coagulopathy. Here, we further show in mouse models that the apoptotic cell-scavenging factor lactadherin, given at a single dose of 400 μg/kg 30 minutes before (preconditioning) or 30 minutes after cerebral fluid percussion injury, prevented coagulopathy as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 40 publications
1
66
0
Order By: Relevance
“…Alternatively, treatments in TBI aimed at clearing brain-derived microparticles that activate platelets and preventing diffuse microthrombus formation have also shown promise by decreasing the incidence of coagulopathy in preclinical models. 41,64 Finally, production of synthetic particles that mimic important platelet functions has been an area of great interest for more than ten years. 65 Platelet-like microparticles have been developed that can stiffen a clot, induce retraction, and decrease susceptibility to fibrinolysis.…”
Section: Novel Therapeutic Approaches To Platelet Dysfunctionmentioning
confidence: 99%
“…Alternatively, treatments in TBI aimed at clearing brain-derived microparticles that activate platelets and preventing diffuse microthrombus formation have also shown promise by decreasing the incidence of coagulopathy in preclinical models. 41,64 Finally, production of synthetic particles that mimic important platelet functions has been an area of great interest for more than ten years. 65 Platelet-like microparticles have been developed that can stiffen a clot, induce retraction, and decrease susceptibility to fibrinolysis.…”
Section: Novel Therapeutic Approaches To Platelet Dysfunctionmentioning
confidence: 99%
“…As a result, these brain‐derived cellular microvesicles initiate and propagate key secondary pathological processes of TBI: endothelial injury, coagulopathy, and inflammation. Because of these detrimental activities, removing cellular microvesicles from the circulation by the apoptotic cell‐scavenging factor lactadherin (milk fat globule–epidermal growth factor 8) has been shown to accelerate microvesicle clearance, to prevent TBI‐induced coagulopathy, and to improve the outcome of TBI in mouse models …”
mentioning
confidence: 99%
“…Because of these detrimental activities, removing cellular microvesicles from the circulation by the apoptotic cell-scavenging factor lactadherin (milk fat globule-epidermal growth factor 8) 22 has been shown to accelerate microvesicle clearance, to prevent TBI-induced coagulopathy, and to improve the outcome of TBI in mouse models. 21,23 Because of their distinct pathogenic pathways, coagulopathy induced by trauma to the body and limbs and hemorrhagic shock and that induced by isolated TBI may require different resuscitation strategies. The timely, judicious, and balanced use of blood-component and fluid resuscitations has been the management of choice for coagulopathy associated with body trauma, especially when hemorrhagic shock is present.…”
mentioning
confidence: 99%
“…Recent studies have suggested that brain-derived extracellular vesicles (BDEVs) may hold the answers to both questions. [12][13][14] Brain-Derived Extracellular Vesicles Trigger Consumptive Coagulopathy TBI-IC has been diagnosed using a variety of clinical tests that define different aspects of hemostasis. 3,10,11 For example, in a study of 972 TBI patients who developed coagulopathy, Ddimer and fibrin degradation products were detected soon after injury followed first by a profound depletion of fibrinogen and then by prolonged prothrombin and partial thromboplastin times.…”
mentioning
confidence: 99%
“…Consistent with this causal role of EVs in TBI-IC, lactadherin (milk fat globule-epidermal growth factor 8), an apoptotic cell-scavenge factor, 22 prevents the development of the systemic hypercoagulable state and improves the neurologic function and survival of mice subjected to severe TBI and those infused with BDEVs by enhancing the clearance of EVs from circulation. 13…”
mentioning
confidence: 99%